The Influence of Entrepreneurial Orientation and Innovation on MSME Performance Mediated by Competitive Advantage - Susi Sugiyarsih; Agus; Rohadin; Aos; Ria Adriyani (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In the current dynamic business environment, small businesses face intense competition that requires strong strategic capabilities to survive and grow. This study examines the effect of entrepreneurial orientation and innovation on the business performance of MSMEs through the competitive advantage. A quantitative approach was employed using survey data from 132 MSMEs, analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that entrepreneurial orientation and innovation have a significant positive effect on competitive advantage. Innovation also has a direct positive effect on business performance, while entrepreneurial orientation does not directly influence performance. Competitive advantage plays a critical mediating role, exerting a strong and significant effect on business performance and transmitting the impact of entrepreneurial orientation and innovation to performance outcomes. These findings imply that MSMEs should prioritize innovation-driven strategies and actively leverage entrepreneurial orientation to build sustainable competitive advantages. Policymakers and business development agencies are encouraged to support MSMEs through innovation capacity building and entrepreneurial capability development, as competitive advantage emerges as a key mechanism for enhancing long-term business performance.